Learning Autodesk Inventor 2008 - Grabowski, Ralph (Delmar Cengage Learning, 2008)
Welcome to 3D modeling as it should be! As an AutoCAD user, you are about to enter a brand-new CAD experience, one where you no longer worry about text sizes, linetype scales, paper space, and plot styles. Instead, you sketch with Inventor, then extrude, assemble-and your 3D model is done! As technical editor Bill Fane puts it, "Inventor lets us get back to 'napkin CAD'." Learning Autodesk Inventor 2008: The 2D to 3D Transition Handbook examines and clearly explains the similarities and differences between AutoCAD and Inventor. The goal is to help the hesitant AutoCAD user jump into Inventor while reassuring users that their valuable collection of AutoCAD drawings can be reused - and even combined - in Inventor and freeing them to go beyond the drawing-with-lines-and-arcs orientation of AutoCAD